The Effect Of E-Service Quality And E-Trust On Buying Interest In Shopee Pay Users In The Millennial Generation - Siti Aisyah; Virgo Simamora; Bobby Reza (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
The use of e-wallet is increasing as online transactions increase in Indonesia. This research is an explanatory study that aims to find out the influence of E-service quality and E-trust on the interest of using ShopeePay when shopping online among Millennials in DKI Jakarta. The population of this study is the entire Generation of Millennials in DKI Jakarta who have used ShopeePay at least three times when making online transactions and the number is unknown. Sampling technique used is purposive sampling techniques on condition samples are Millennial Generation, live in the territory of DKI Jakarta and have used ShoppePay at least 3 times. Data collected through the spread of the google form questionnaire to the Millennial Generation. Data analysis using SmartPLS 3.0 Partial Least Squares Structural Equation Modeling (PLS-SEM). Research results show that E-Service Quality and E-Trust have a positive and significant influence on purchasing interest using ShopeePay on the millennial generation in DKI Jakarta. According to research results, 92.9% of Millennial Generation interest in using ShoppePay is influenced by E-Service Quality and E-Trust. The findings confirm that it is important for e-wallet service providers to focus on improving the quality of electronic services and building user confidence to boost purchasing interest.